Legal analysis of marriage, its dissolution and the distribution of the inheritance in "El divorcio de la condesita" by Ricardo Palma - Aguilar Laura, Xiomara Luz (2022)
This article will analyze, from a legal perspective, the story «El divorcio de la condesita», by Ricardo Palma, who in this text narrates the life of Marianita, a thirteen year old girl who is forced to marry Count Dávalos, a man over sixty years old. Subsequently, Marianita manages to avoid the cohabitational consummation of the marriage, escaping and taking refuge in a convent to then file a divorce suit, a dispute that ends with the death of the count, and this fact causes Marianita to receive her late husband’s inheritance. In this sense, this paper will develop the legal acts of marriage, its dissolution and inheritance, as well as the social notions that were held during the viceregal era and the changes that acquired or remain until today.